The Role of Coach-Athlete Interpersonal Communication in Enhancing Athletic Performance at Cendana Judo Club - Daffa Nando Ferdiansyah; R. Ayu Erni Jusnita; Nurul Suhesti (Westscience Press, 2026)
Interpersonal communication plays a crucial role in athlete development because it influences motivation, psychological well-being, and athletic achievement. This study aimed to analyze how interpersonal communication between coaches and athletes contributes to performance development within the Cendana Judo Team in Surabaya. A qualitative descriptive approach was employed involving one head coach, one assistant coach, and four active athletes selected through purposive sampling. Data were collected through semi-structured interviews, participant observation, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings revealed three major themes: openness and trust as the foundation of coach-athlete relationships, interpersonal communication as psychological support and a source of motivation, and communication as a contributing factor to athletic achievement. Effective communication strengthened discipline, commitment, mental readiness, and performance. Sports organizations should prioritize communication competence development and structured support systems.